Perceptions of Spanish-language COVID-19 video messaging among the Hispanic community: A qualitative study in the United States of America - Grace Ellen Brannon; Karishma Chatterjee; Chyng-yang Jang; Charla Markham Shaw; Vinicio Sinta; Julian Rodriguez (PLoS ONE, 2026)
With evidence linking credible and quality COVID-19 vaccine information to positive vaccination attitudes and intentions, it's vital to understand how communities facing health disparities access health information about COVID-19. This interview study of 49 Hispanic individuals in a large southern suburban county is a part of a larger three-year multi-method study. Through the lens of self-determination theory, this project investigates perceptions of four television-aired Spanish-language video messages on CseOVID-19 vaccination developed from findings of prior local focus groups and panel surveys supported by community partners. The present study’s findings show human-centered, gain-frame messaging was positively received and highlight the need for targeted Spanish-language public health messaging in Spanish news media to improve quality information about COVID-19. Gentler suggestions for health protective behaviors may foster greater perceived resonance, credibility, and informational value of public health messages, with potential implications for psychological reactance and subsequent responses.